Predicting COVID-19 Incidence Using Wastewater Surveillance Data, Denmark, October 2021–June 2022 - Oliver McManus; Lasse Engbo Christiansen; Maarten Nauta; Lene Wulff Krogsgaard; Naja Stolberg Bahrenscheer; Lene Mia von Kappelgaard; Tobias Christiansen; Mikkel Fougt Hansen; Nicco Claudio Hansen; Jonas Kähler; Anders Mølgaard Rasmussen; Stine R. Richter; et al. (2023)
Analysis of wastewater is used in many settings for surveillance of SARS-CoV-2, but it remains unclear how well wastewater testing results reflect incidence. Denmark has had an extensive wastewater analysis system that conducts 3 weekly tests in ≈200 sites and has 85% population coverage; the country also offers free SARSCoV- 2 PCR tests to all residents. Using time series analysis for modeling, we found that wastewater data, combined with information on circulating variants and the number of human tests performed, closely fitted the incidence curve of persons testing positive. The results were consistent at a regional level and among a subpopulation of frequently tested healthcare personnel. We used wastewater analysis data to estimate incidence after testing was reduced to a minimum after March 2022. These results imply that data from a large-scale wastewater surveillance system can serve as a good proxy for COVID-19 incidence and for epidemic control.